Social integration of unemployed immigrants : a comparison of integration programs in Jyväskylä and Reykjavík - Johanna Ann-Louise Carin Läärä 1986- (2012)
People have always migrated to different countries but their motivations vary. Whatever the reasons are for immigration, everyone has to face the difficult task of integration. Integration is not an easy process, especially if one is from a culture completely different from the host country’s. The purpose of integration is to become a full member of a host country’s society, which means that one needs to know the language and the culture in order to function fully within the society. To ease this process, many countries have developed special programs for immigrants where they teach the language that is spoken in the country and basic knowledge about the society such as the majority’s culture, educational system, welfare system and so on. With the tools offered by the integration programs, immigrants are supposed to be able to find jobs for themselves or a job that is suitable for their education. Both Iceland and Finland offer such courses. The purpose of this study is to explore and compare immigration policies and the integration programs in Jyväskylä, Finland and Reykjavík, Iceland to find out how unemployed immigrants are aided in their integration process in a new society. The study compares and contrasts the immigration policies and integration programs in Finland and Iceland. The two towns were chosen for the study because of their similarities; language skills in Finnish and Icelandic are highly emphasized and unemployment rate is currently high in both places, further necessitating good language skills. Findings suggested that type of immigration and integration policies and hence integration programs are quite different from each other. Finland has formed its integration programs to fulfil the needs of unemployed immigrants, integration process is considered to be long and language and culture are taught together. Iceland sees integration process as a short event because it has formed the courses for employed immigrants. Culture and language were also taught separately. Fólk hefur alltaf flutt til ...